Sustainable Geopark Tourism Destination Development Strategy - Jannah, Miskol; Rahmanita, Myrza; Amaniati, Fetty (Sahabat Publikasi, 2025)
This study aims to evaluate strategies for developing a sustainable geopark-based tourism destination in Air Batu Village, Merangin Regency, Jambi Province. The village is part of the Merangin Geopark area, which is known for its significant geological wealth, such as the presence of ancient plant fossils and unique natural landscapes. However, the development process of this tourism area still faces several obstacles, including limited infrastructure, low levels of community engagement, and suboptimal coordination between the village government and the Tourism Awareness Group (Pokdarwis). This research adopts a qualitative approach, utilizing data collection techniques such as direct observation, in-depth interviews, and documentation. Data analysis is conducted using the SWOT method to explore the strengths, weaknesses, opportunities, and threats related to sustainable geopark tourism development. The findings indicate that development efforts can be improved through cross-sector collaboration involving the government, local communities, and the private sector. The main focus should be directed toward enhancing supporting infrastructure, promoting the destination effectively, and strengthening the local economy based on its existing potential. This study is expected to provide constructive input for the formulation of strategic policies in the sustainable management of the Merangin Geopark and serve as an important reference for future related research.